Water-resource and land-use issues - Calder, I.R.C. (International Water Management Institute, 1998)
This paper reviews perceived notions of the relationships between catchment land use and hydrology and explores whether much of the widely disseminated folklore, so often inextricably linked with issues of land use, is based on myth or reality. Gaps in our knowledge of the underlying processes in relation to land use and hydrology are identified. Our ability to apply this knowledge at different scales ranging from the plot to the catchment and regional scales are discussed and specific examples are drawn from Indian and African case studies. Methods for linking spatially distributed land-use hydrological models with economics and ecology through decision support systems are outlined and proposed as a framework for the integrated management of land and water developments at the catchment scale.